Numerical simulation and experimental validation of oil shale drying in pneumatic conveying dryer. Issue 5 (4th April 2018) - Xia, Liangzhi; Zhang, Hongchun; Wang, Baohe; Yu, Caiyuan
ABSTRACT: Oil shale is an important unconventional energy and has enormous reserves in the world. However, the high moisture content impedes its utilization in the restoration and combustion process. This paper explores experimental and numerical studies on the drying performance of the Liu Shu River oil shale in a pneumatic conveying dryer (4.8 cm ID, 1.8 m high). The experiments were carried out under the different operation conditions. The 3-D modeling was done with a computational fluid dynamics package, in which the gas phase is modeled as a continuum using Euler approach, and the particle phase is modeled by a discrete phase model with a Lagrangian approach. The effects of inlet air velocity, particle size, solid mass flow rate, and inlet air temperature on the drying performance of oil shale particles are investigated. It is found that the simulated values are in good agreement with experimental data. The developed model of is thus suitable to describe the oil shale pneumatic drying process. Generally, it is concluded that the moisture evaporation occurs mainly at the constant rate drying stage in the pneumatic drying process due to very short residence time. The drying rate increases as the inlet air velocity and temperture increase, while increasing the particle size or the solid mass flow rate decreases the drying rate. It is the breakthrough to improve the drying efficiency by increasing the slip velocity and extending pariticle residence time in the dryer. Gas temperature and particle size have the significant influence on degree of particle drying. But the mass flow rate and gas velocity are the important parameters for the energy efficiency in the drying process.